The Solution Properties Of Liquid Detergent Modified With Carboxymethyl Cellulose From Banana Pseudo Stem - Oseh, Ikechukwu Harrison; Nwokocha, Louis M (Tropical Scientific Journal, 2025)
Objective: Carboxymethyl cellulose (CMC) can be used as thickener and rheology modifier in liquid detergents. In this research, liquid detergent of known concentration was prepared and the effect of CMC of different degrees of substitution (D.S) on the rheological properties and cleaning action of the liquid detergent was studied. Research Method: The banana pseudo stems were converted to cellulose when pulped with sodium hydroxide (NaOH) solution bleached with sodium hypochlorite and dried. The cellulose was converted to CMC of different D.S by reaction with different amounts of chloroacetic acid in the presence of NaOH as alkalizing agent. Detergent was prepared by neutralizing 2-dodecylbenzene sulphonic acid with NaOH in the molar ratio of 2:1. The liquid detergent (1%, w/v) was modified with CMC of different D.S. The liquid detergent was characterized in terms of pH, lather volume, foam capacity, rheology and cleaning action. Findings: The CMC prepared had D.S in the range of 0.67 to 0.91. The pH of 1% (w/v) aqueous detergent was 6.12. The lather volume and foam capacity of 1% (w/v) liquid detergent were 70.20mL and 3.51 respectively in distilled water and 51.30mL and 2.57 respectively in hard water. The rheological behaviors of the liquid detergent modified with CMC of different D.S were non-Newtonian. Originality: The liquid detergent modified with CMC had better cleaning action and increased with D.S. Liquid detergent with known concentration was produced and CMC from banana pseudo modified the rheological properties of liquid detergent with increased D.S. The CMC also increased the cleaning action of the liquid detergent.